Murakami T : the t-shirts I love - Murakami, Haruki, 1949- (Alfred A. Knopf, 2021)
"The international literary icon opens his eclectic closet: Here are photographs of Murakami's extensive and personal T-shirt collection, accompanied by essays that reveal a side of the writer rarely seen by the public. Considered "the world's most popular cult novelist" (The Guardian), Haruki Murakami's books have galvanized millions around the world. Many of his fans know about his 10,000 vinyl record collection, and his obsession with running, but few have heard about a more intimate, and perhaps more unique, passion: his T-shirt collecting habit. In Murakami T, the famously reclusive novelist shows us his T-shirts--including gems from the Springsteen on Broadway show in NYC, from The Beach Boys concert in Honolulu to the shirt that inspired the beloved short story, "Tony Takitani." Accompanied by short, frank essays that have been translated into English for the first time, these photographs reveal much about Murakami's multifaceted and wonderfully eccentric persona"--